“I’m not homosexual or heterosexual, I’m paedosexual”: exploring sexual preference for children using interpretive phenomenology - Duff, Simon (Emerald, 2017)
Purpose: There is little research that examines the experiences of individuals who were assessed as having a sexual preference for children. The purpose of this paper is to investigate the lived experience of five incarcerated participants who possessed a sexual preference for either prepubescent or pubescent children and had completed an accredited programme for males convicted of sexual offences in HM Prison Service in England and Wales.